Apelacja obrońcy węzła małżeńskiego w procesie skróconym o stwierdzenie nieważności małżeństwa - Kamiński Rafał (Ius Matrimoniale, 2018)
The application for appeal against the judgment is also possible in the so-called processus brevior, a shortened form of the trial for the nullity of marriage, which takes place before the bishop. It is obvious that the economy of the shortened process can not be in contradiction with the fundamental right to a just judgment and its challenge if the party does not consider it so. Despite the postulated speed of the process, this right must be preserved. In the case of the appeal of the defender of the bond, in the face of the abolition of the requirement of two identical judgements, we additionally deal with the defense of the sacrament of marriage as a public good. This is in the interest of the Church, which is protected by appealing the judgement. The specificity of the processus brevior, consisting in its simplification and acceleration of the procedures, obviously requires the use of specific norms set for it, different from those that govern the ordinary process. This applies to the jurisdiction of the appellate tribunal, confirmation of the bishop’s judgment and the admission itself, or the possibility of rejecting the appeal a limine. The remaining requirements for the appeal in the processus brevior are identical to those that the legislator asks the ordinary in the ordinary process. However, they refer to the presentation of the appeal, its support, and statutory deadlines for accomplishing this. The appeal of the defender of the bond in the processus brevior has a special meaning, because most often with such, if it occurs, we will have to deal with procedural practice. This is supported by the consistent demand of private parties that appear to be interested in obtaining pro nullitate judgement, which is the only one that can be issued by the bishop before which the proceedings are pending.